The simultaneous emergence of free exciton emission and d0 ferromagnetism for undoped ZnO nanoparticles. Issue 87 (5th September 2016) - Ghose, Srabantika; Gogurla, N.; Ranganathan, R.; Jana, D.
Abstract : Free excitonic emission is observed for the ferromagnetic undoped ZnO nanoparticles prepared by mechanical milling. Abstract : d 0 ferromagnetism (FM) in undoped ZnO nanoparticles is a subject of intense interest nowadays due to its potential application in the field of spintronics. In the last three years this topic has taken a new turn as a defect induced transition of magnetic property from diamagnetic to weakly ferromagnetic has been observed for mechanically milled ZnO nanoparticles. In this report low temperature (LT) photoluminescence (PL) measurements have been carried out for the first time on these ferromagnetic ZnO nanoparticles to unveil the reason for this magnetic transition. Usually ZnO nanoparticles are diamagnetic and show dominant donor-bound exciton (DX) emissions at low temperatures. In this study we have observed a quenching of DX emission and the dominant evolution of free exciton (FX) emission for the ZnO nanoparticles having d 0 FM. Interestingly here FX emission has been observed for more defect enriched samples. A Raman scattering (RS) study indicates a significant modification of phonon states especially in the surface regions of the ferromagnetic nanoparticles. In this context, the effect of exciton–phonon coupling on the delocalization of bound excitons at the defect enriched surfaces of ZnO nanoparticles has been illustrated. The effect of long range correlation of free excitons on the magnetic properties has also been discussed on this concern.